2021
DOI: 10.3390/w13162178
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Preferences of Visitors to the Danube Floodplains National Park, Vienna

Abstract: Successfully managing heavily visited protected riverscapes requires information about visitor preferences for the social, biophysical and infrastructural attributes of river landscapes. This study analyzed the landscape preferences of 520 on-site visitors to the peri-urban Danube Floodplains National Park using an image-based discrete choice experiment. The study explored the effects of various landscape types (water bodies, terrestrial landscapes), recreational infrastructures (trail types, facilities) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…It was examined in our study what kind of stands the national park visitors would prefer for different activities. More fruitful results can be achieved not only by the texts telling about the social and economic benefits of forest areas but also the integration of this information with the photos depicting the forest ecology (Arnberger et al 2021). Although visitors mainly preferred certain stands for certain recreational activities through images shown, we do not know whether they will actually visit and use these sites for those certain recreations.…”
Section: Discussionmentioning
confidence: 99%
“…It was examined in our study what kind of stands the national park visitors would prefer for different activities. More fruitful results can be achieved not only by the texts telling about the social and economic benefits of forest areas but also the integration of this information with the photos depicting the forest ecology (Arnberger et al 2021). Although visitors mainly preferred certain stands for certain recreational activities through images shown, we do not know whether they will actually visit and use these sites for those certain recreations.…”
Section: Discussionmentioning
confidence: 99%
“…Meadows in combination with floodplain forests were rated as the most preferred landscape section by visitors in a landscape preference study in the Viennese part of the DANP [5]. Meadows have been part of the DANP landscape for centuries, and long-term visitors may be accustomed to seeing them in the DANP.…”
Section: Discussionmentioning
confidence: 99%
“…Research on public river preferences has demonstrated that humans prefer larger bodies of open water, natural river landscapes, and fast-flowing streams, while they dislike dead wood in rivers, algae blooms, and muddy water [22][23][24][25]. An image-based preference study asking visitors to the DANP found that natural features, such as floodplain forests in combination with meadows or xeric alluvial biotopes, alleys of trees and gravel trails were preferred, while dense forests, open agrarian structures, and water bodies with 50% reed cover were less preferred [5]. Another Austrian study found that pupils had rather positive attitudes towards and perceptions of natural rivers; nevertheless, few of them perceived natural rivers as useless wilderness [8].…”
Section: River Landscape Preferences and Perceptionsmentioning
confidence: 99%
See 2 more Smart Citations